Prediction of the invasiveness of PTMC by a combination of ultrasound and the WNT10A gene - Yan, Zhang; Gang, Liu Wen; Yan, Guo Shi; Zhou, Ping (Frontiers in Endocrinology, 2022)
Objective The purpose of this study was to predict the invasiveness of papillary thyroid microcarcinoma (PTMC) via ultrasonography in combination with the Wnt family member 10A (WNT10A) gene to provide a reference basis for evaluating the invasive capability of PTMC. Methods Cancer tissue were collected from 182 patients with unifocal PTMC, and the patients were divided into the invasive group and the non-invasive group based on whether the lesions invaded the thyroid capsules or whether lymph node metastasis occurred. The expression of WNT10A protein was examined. Age, sex, maximum nodule diameter, color Doppler flow imaging (CDFI), nodule echo, microcalcification, aspect ratio, morphology (boundary), nodule location, internal structure, ultrasound-suspected lymph node metastasis (US-LNM), and WNT10A expression were compared between the invasive group and the non-invasive group. Univariate analysis and multivariate logistic regression analysis were performed, and a p value of less than 0.05 indicated that the difference was statistically significant. Results (1) 36 patients in the non-invasive group showed high expression and 66 patients showed low or no expression, while 54 patients in the invasive group showed high expression and 26 patients showed low or no expression, suggesting that the expression level of WNT10A was higher in the invasive group than in the non-invasive group, with a statistically significant difference between the two groups (P<0.01). (2) Univariate analysis showed that there were statistically significant differences between the invasive PTMC group and the non-invasive group in age, sex, maximum nodule diameter, microcalcification, US-LNM and high WNT10A expression. (3) Multivariate analysis showed that the risk factors for invasiveness in patients with PTMC included age < 45 years, maximum nodule diameter > 7 mm, microcalcification, US-LNM and high WNT10A expression. Conclusion The risk factors for PTMC invasiveness included age < 45 years, maximum nodule diameter >7 mm, microcalcification, US-LNM and high WNT10A expression. A combination of ultrasonography and WNT10A gene analysis could provide a reference basis for evaluating the invasive capability of PTMC.